Physiological parameters of a high intensity intermittent calistenic exercise in advanced practitioners (Research, Society and Development, 2021)
High intensity intermittent calisthenic exercise (ECIAI) is considered an effective and low cost method for improving physical fitness and body composition. The aim of the study was to evaluate the acute effects of an ECIAI session on subjective perception of effort (RPE), oxygen saturation (SpO2) and hemodynamic variables in advanced practitioners. 8 men practicing Cross Training and CrossFit® were evaluated. The protocol consisted of 4 sets with maximum executions for 30 seconds, followed by 2 minutes of rest. PSE was assessed immediately after each series. SpO2, heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured at rest and immediately after each series. Values ​​were expressed as the mean ± standard deviation from the mean. There were no differences between series in PSE. There was an increase in HR (bpm) after series 1, 2, 3 and 4. As for SBP (mmHg), an increase was observed after series 2 and 3 when compared to rest. The DBP (mmHg) was not changed. MAP (mmHg) increases immediately after series 2 and 3 when compared to rest. The Double Product also increased immediately after all series when compared to rest. The results of the present study indicate that ECIAI promoted important cardiorespiratory adjustments in adults with experience in this type of exercise. These effects characterize a vigorous physical effort and reinforce the importance of the physiological control of the internal load during the training session.